Grain Sorghum Yield Response to Water Availability—North Central Kansas Experiment Field - J. P. Broeckelman; G. J. Kluitenberg; K. Roozeboom; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2015)
Yield effects of irrigation on sorghum and corn were compared, focusing only on the grain sorghum phase. Average water use for irrigation was 22 in., and dryland sorghum used 17 in. Average yields based on 12.5% grain moisture for dryland and irrigated sorghum were similar, with 138 bu/a for the irrigated and 142 bu/a for the dryland environment. Irrigated sorghum yields were similar, but in dryland, the Pioneer 84G62 hybrid yielded 149 bu/a, a 10 bu/a increase over Pioneer 84Y50 and DKS 53-67 hybrids, which yielded 139 bu/a and 138 bu/a, respectively. Although there was a difference in the yield between the hybrids on the dryland block, there were no significant differences between water use and water use efficiency (WUE).
Keywords: sorghum; water use; irrigation; dryland; yield